Factors associated with uninvestigated dyspepsia in students at 4 Latin American schools of medicine: A multicenter study - Talledo-Ulfe, L (2018)
Introduction and aims: Dyspepsia is a multifactorial disease that can involve alcohol, tobacco, or nonsteroidal anti-inflammatory drug use, as well as lifestyle, diet, socioeconomic elements, or psychologic factors. The aim of the present article was to establish the frequency of uninvestigated dyspepsia and determine its associated factors in students at 4 Latin American schools of medicine. Materials and methods: A cross-sectional, analytic study was conducted, in which a survey made up of closed-ended questions was applied at just one point in time. The association between the variables was then analyzed. A new questionnaire for the diagnosis of dyspepsia was one of the tests utilized to diagnose uninvestigated dyspepsia. Generalized linear models were used for the bivariate and multivariate analyses, employing the Poisson model with the log link function, obtaining crude prevalence ratios, adjusted prevalence ratios, and their 95% confidence intervals. Results: Of the 1,241 individuals surveyed, 54% (841) were females and the median age was 21 years (range: 19-23 years). Prevalence of uninvestigated dyspepsia was 46%. The factors that had a direct association with dyspepsia were: depression, difficulty sleeping, and coffee consumption. On the contrary, eating regularly in a boarding house and the mate sex had an inverse association. Conclusions: Uninvestigated dyspepsia frequency was high in students at 4 Latin American schools. Depression, difficulty sleeping, and steady coffee drinking were factors directly associated with dyspepsia, whereas male sex and eating out at regular hours were factors with a reverse association. Therefore, we recommend that universities implement early detection programs for this highly preventable pathology. Published by Masson Doyma Mexico S.A. on behalf of Asociacion Mexicana de Gastroenterologia. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).